Novel zein‐based multilayer wound dressing membranes with controlled release of gentamicin. Issue 6 (21st December 2018) - Kimna, Ceren; Tamburaci, Sedef; Tihminlioglu, Funda
Abstract: Recently, functional multilayer scaffolds with controlled drug release ability come into prominence for wound healing applications to mimic the layered structure of skin tissue and prevent the possible infections at the defect site. In this study, controlled antibiotic releasing zein bilayer membranes were fabricated for treatment of acute skin infections. Gentamicin loaded fibers were prepared by electrospinning on the membrane surface. Membranes were characterized with scanning electron microscope, atomic force microscopy, Fourier transform infrared spectroscopy, contact angle, mechanical analysis, swelling, degradation, and water vapor permeability studies. In vitro cytotoxicity, cell attachment, and proliferation were investigated. Cell attachment on fiber layer was observed with fluorescence imaging. Fabricated fibers showed structural similarity to the skin tissue layers with a fiber diameter range of 350–425 nm and film thickness in the range of 311–361 μm. Mechanical properties were found compatible with the skin tissue. In addition, membranes showed antimicrobial activity against Staphylococcus aureus and Escherichia coli . The sustained release was achieved with a cumulative release of 94%. Membranes did not show any cytotoxic effect. NIH/3T3 and HS2 cell lines were proliferated on each layer mimicking the multilayer skin tissue. Hence, zein‐based bilayer membrane showed promising properties to be used as a potential antimicrobial wound dressing for skin tissue regeneration. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 2057–2070, 2019.